Polsko-ukraińskie małżeństwa mieszane – między przeszłością a współczesnością. Uwagi na marginesie życia w Białym Borze - Kosiek, Tomasz (Wydawnictwo Uniwersytetu Jagiellońskiego, 2018)
The author of the article tackles the subject of Polish-Ukrainian mixed marriages in Poland. He shows the changes that have taken place concerning the scope of the marital models utilised within the Ukrainian community. He begins his musings looking at the Polish-Ukrainian borderlands in the 19th and the beginning of the 20th centuries. It comes to light that mixed marriages were at that time a common and accepted phenomenon in small, local communities. The end of openness towards mixed marriages was brought by the “Vistula” Operation, as a result of which historic Ukrainian and Polish-Ukrainian neighbouring communities from south-eastern Poland were destroyed, with the people making them up being resettled in the so-called Recovered Territories. In this new context, Ukrainian communities began to work out new marital models, according to which the aim was to enter into marriages within one’s own group. In order to achieve endogamy on the one hand within Ukrainian families, clear pressure began to arise upon the marital choices of the young, on the other hand, the entire community had worked out a series of strategies aimed at helping to achieve the behaviour patterns expected by the Ukrainian group.
Keywords: mniejszość ukraińska; małżeństwa mieszane; stosunku polsko-ukraińskie; sąsiedztwo; asymilacja; endogamia